Narrative Environment of Malgudi: Space, Autonomy, and Belonging - Gouthaman K J; Nandini Pradeep J (IAFOR Journal of Arts & Humanities)
A world, real or fictional, the entities that compose the world, and their relations with each other exist and undergo changes in space and time. The paper explores the interactions between space and social structures that affect the lives of the inhabitants of a narrative world; the effects of a narrative environment on the subjectivities and social lives of characters. R. K. Narayan's short stories reveal multifarious relations within space; socially produced, politically re-shaped, and inherently contested. Autonomy and belonging of the characters are either facilitated or threatened by the existence of varied spaces, the inherent contemporaneous heterogeneity, scrutinized at distinct levels in different narratives. The short stories highlight how the life of an individual in Narayan’s fictional town Malgudi is transformed due to the changes in the narrative environment, when space is reshaped by personal, societal, or, political motives. The narratives critically explore the sacralization (a reversal of profanation) of spaces that suddenly excludes the ordinary, representing the transformation of public spaces freely used by people into exclusionary, or sacred, spaces. The paper investigates how the transformation of spatial relations and its dynamic impact in the narrative environment reveals the complex interplay between space, power, identity, and autonomy.